232k views
3 votes
Consider the equation 5 – 3(2x – 7) = 12 – 5(x – 2). Is x = 2 a solution to this

equation? Is x = 4 a solution to this equation? Explain your reasoning in each case

1 Answer

1 vote

Answer:

see below

Explanation:

5 – 3(2x – 7) = 12 – 5(x – 2)

Substitute x=2

5 – 3(2*2 – 7) = 12 – 5(2 – 2)

5 – 3(-3) = 12 – 5(0)

5 - 3*(-3) = 12

5+9 = 12

14=12

This is false so it is not a solution

5 – 3(2x – 7) = 12 – 5(x – 2)

Substitute x=5

5 – 3(2*4 – 7) = 12 – 5(4 – 2)

5 – 3(8-7) = 12 – 5(2)

5 - 3*1 = 12-10

5-3 = 2

2=2

This is true so it is a solution

User Asher Hawthorne
by
5.7k points